Relationships between urina lithogenicity and neuro-humoral-immune factors in patients with chronic pyelonephrite and cholecystite - B V Hrinchenko; O V Snihur; V R Flyunt; W Zukow (Kazimierz Wielki University, 2015)
Hrinchenko B V, Snihur O V, Flyunt V R, Zukow W. Relationships between urina lithogenicity and neuro-humoral-immune factors in patients with chronic pyelonephrite and cholecystite. Journal of Education, Health and Sport. 2015;5(5):44-51. ISSN 2391-8306. DOI: 10.5281/zenodo.17369 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A44-51 https://pbn.nauka.gov.pl/works/557141 http://dx.doi.org/10.5281/zenodo.17369 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 15.04.2015.   RELATIONSHIPS BETWEEN URINA LITHOGENICITY AND NEURO-HUMORAL-IMMUNE FACTORS IN PATIENTS WITH CHRONIC PYELONEPHRITE AND CHOLECYSTITE   B V Hrinchenko1, O V Snihur1, V R Flyunt1,2, W Zukow3   1JSC "Dnipro-Beskyd", Truskavets', Ukraine t.verdo@mail.ru 2Laboratory of Balneology, OO Bohomolets' Institute of Physiology, Truskavets', Kyiv, Ukraine 3Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   SUMMARY Objective. Despite a long history of research questions about the factors that determine lithogenicity urine remains open. Aim: to evaluate lithogenicity urine of patients with chronic pyelonephritis and cholecystitis and find her relationships with a concentration both in urine and plasma electrolytes and nitrogenous metabolites and the parameters gall-bladder motility, HRV, EEG and Immunity. Results. Lithogenicity urine Index (Lith) calculated by the formula: Lith=(Oxalates•Uric acid•Calcium/Magnesium•Creatinin)0,2, is determined positive by Oxalates (r=0,55) and Uric acid (r=0,34) but negative by Creatinin (r=-0,54) and Magnesium (r=-0,32). Revealed significantly correlation Lith with Uric acid Plasma level (r=-0,30) and Gall-bladder postprandial Volume, most 30 min (r=-0,51). Discovered unexpectedly negative correlation Lith with both Baevskiy Stress Index (r=-0,33) and Sympatho-Vagal Balance Index HRV (r=-0,36). Among EEG parameters correlated with Lith δ-rhythm amplitude (r=-0,50), θ-rhythm asymmetry index (r=0,45) and α-rhythm frequency (r=0,32). Among parameters of Immunity correlated with Lith blood levels of CD19+ B-Lymphocytes (r=0,34) and CD16+ NK-Lymphocytes (r=0,30). Canonical correlation between urina Lithogenicity and Neuro-Humoral-Immune factors is veri strong: R=0,97. Conclusion: in patients with chronic pyelonephritis and cholecystitis there are relationships between urina Lithogenicity and neuro-humoral-immune factors. Keywords: lithogenicity urine, neuro-humoral-immune factors, men.